Evolutionary Game Analysis of the Stress Effect of Cross-Regional Transfer of Resource-Exhausted Enterprises - Hui Yu; Wei Wang; Baohua Yang; Cunfang Li (Complexity)
This paper analyses the stress effect of cross-regional transfer of resource-exhausted enterprises from eastern China to central and Western China. A tripartite evolutionary game model including the central government, the local government of the operation recipient region, and the resource-exhausted transfer enterprises is established under the assumption of limited rationality. By analysing the evolutionary equilibrium and using MATLAB, for example, analysis, the relationship between equilibrium probability and various parameters, as well as the key influencing factors of equilibrium strategy were explored. The research shows, first, that the degree of punishment imposed by the central government on the local governments, the implementation of regulation by the local governments, and the amount of rewards/punishments implemented by the local governments for transfer enterprises are the key factors affecting evolutionary stability. Second, it shows that the local governments’ penalty for transfer enterprises has a significant impact on the convergence speed of enterprises’ strategic choice to “Completely Control Pollution.” Finally, from the perspective of the relationships between the central government and the local governments, as well as with transfer enterprises, countermeasures and suggestions are put forward to effectively prevent the stress effect of the cross-regional transfer behaviour of resource-exhausted enterprises.